A scoping review of the research evidence of the developmental assets model in Europe - Martin-Barrado, Antonio David; Gomez-Baya, Diego (Frontiers in Psychology, 2024)
Positive Youth Development (PYD) is a strength-based perspective that focuses on the resources to promote a successful transition to adulthood, derived from the Relational Developmental Systems theory. In this line, the Developmental Assets (DA) model focuses on describing the personal resources (Internal Assets) and contextual resources (External Assets) that help to reach PYD. Most research from this approach has been carried out in United States and, to a lesser extent, in the European continent. The aim of this scoping review was to examine the evidence collected for the DA model in Europe. Web of Science database was used to search for articles published between 2013 and February 2024. Initially, there were 55 possible articles to be included, but after applying the exclusion criteria, this number was reduced to 11. The findings suggested that the evidence for DA in Europe was in line with North American research, so that a higher presence of DA was related to higher well-being, better psychological adjustment, and lower risk behaviors. Internal Assets were the most influential assets, with the Positive Identity category being especially remarkable. Commitment to Learning and Social Competencies were also highlighted in the studies included in the review. Concerning External Assets, Positive Boundaries-expectations and Empowerment were emphasized as protective factors in youth development. These assets were found to present a protective effect against risk behaviors and were positively associated with PYD and socioemotional skills. Thus, these findings support the applicability of the DA framework in promoting PYD in European context, and some intervention strategies are discussed considering cultural diversity.